A study on electromagnetic interference analysis and suppression method for traction system of high-speed EMU - YANG Deyong; ZHU Bingquan; CHEN Ying; ZHI Yongjian; YUAN Keliang; YAN Guanglin (机车电传动)
According to the complexity of electromagnetic interference of traction system of high-speed EMU, and in combination with the design of the vehicle system, the EMI coupling paths of traction system were analyzed. Based on the equivalent interference source method, a calculation model for the common-mode interference of the system was established. The high-frequency test and modeling of the EMU traction system and the simulation prediction of the interference current were completed, and the accuracy of the theoretical model was verified by the measured results. Finally, according to the analysis of the influencing factors of electromagnetic interference of traction system, an interference suppression method was proposed, and the effectiveness of each suppression measure was verified by simulation or test.